Active commuting to and from university, obesity and metabolic syndrome among Colombian university students - Antonio García-Hermoso; Andrea P. Quintero; Enrique Hernández; Jorge Enrique Correa-Bautista; Mikel Izquierdo; Alejandra Tordecilla-Sanders; Daniel Prieto-Benavides; Carolina Sandoval-Cuellar; Katherine González-Ruíz; Emilio Villa-González; Robinson Ramírez-Vélez (BMC, 2018)
Abstract Background There is limited evidence concerning how active commuting (AC) is associated with health benefits in young. The aim of the study was to analyze the relationship between AC to and from campus (walking) and obesity and metabolic syndrome (MetS) in a sample of Colombian university students. Methods A total of 784 university students (78.6% women, mean age = 20.1 ± 2.6 years old) participated in the study. The exposure variable was categorized into AC (active walker to campus) and non-AC (non/infrequent active walker to campus: car, motorcycle, or bus) to and from the university on a typical day. MetS was defined in accordance with the updated harmonized criteria of the International Diabetes Federation criteria. Results The overall prevalence of MetS was 8.7%, and it was higher in non-AC than AC to campus. The percentage of AC was 65.3%. The commuting distances in this AC from/to university were 83.1%, 13.4% and 3.5% for < 2 km, 2-5 km and > 5 km, respectively. Multiple logistic regressions for predicting unhealthy profile showed that male walking commuters had a lower probability of having obesity [OR = 0.45 (CI 95% 0.25-0.93)], high blood pressure [OR = 0.26 (CI 95% 0.13-0.55)] and low HDL cholesterol [OR = 0.29 (CI 95% 0.14-0.59)] than did passive commuters. Conclusions Our results suggest that in young adulthood, a key life-stage for the development of obesity and MetS, AC could be associated with and increasing of daily physical activity levels, thereby promoting better cardiometabolic health.